2010
DOI: 10.1051/0004-6361/201014576
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar OH+, H2O+and H3O+along the sight-line to G10.6–0.4

Abstract: We report the detection of absorption lines by the reactive ions OH + , H 2 O + and H 3 O + along the line of sight to the submillimeter continuum source G10.6−0.4 (W31C). We used the Herschel HIFI instrument in dual beam switch mode to observe the ground state rotational transitions of OH + at 971 GHz, H 2 O + at 1115 and 607 GHz, and H 3 O + at 984 GHz. The resultant spectra show deep absorption over a broad velocity range that originates in the interstellar matter along the line of sight to G10.6−0.4 as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(88 citation statements)
references
References 28 publications
3
85
0
Order By: Relevance
“…The protonated water molecule H 3 O + was first detected much earlier, using the National Radio Astronomy Observatory 12m telescope toward Orion KL and OMC-1 ( 8 , 9 ). Furthermore, all of these molecular ions were found along the line of sight toward the submillimeter continuum source G10.6-0.4 (W31C) using the Herschel Heterodyne Instrument for the Far Infrared ( 10 ). Since OH + and H 2 O + are known to react exothermically with H 2 , both ions are believed to reside in environments with a low fraction of molecular to atomic hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The protonated water molecule H 3 O + was first detected much earlier, using the National Radio Astronomy Observatory 12m telescope toward Orion KL and OMC-1 ( 8 , 9 ). Furthermore, all of these molecular ions were found along the line of sight toward the submillimeter continuum source G10.6-0.4 (W31C) using the Herschel Heterodyne Instrument for the Far Infrared ( 10 ). Since OH + and H 2 O + are known to react exothermically with H 2 , both ions are believed to reside in environments with a low fraction of molecular to atomic hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The water cation is found in naturally occurring plasmas, for instance, in the Earth's ionosphere [1,2], in comet tails [3,4], and in several regions of the interstellar medium [5][6][7][8]. In these plasmas water ions participate in reactions that influence the thermal and chemical properties of the environment as formulated in several model chemistries [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase routes to these species are controversial, but we have shown that an assumed reaction involving efficient hydrogenation of nitrogen at surfaces could readily account for the NH abundance without adverse chemical consequences [28]. However, no [29]. Conventional ion-molecule gas-phase chemistry involving O + ions appears capable of accounting for the observed abundances of these species.…”
Section: (B) Other Reactions On Dustmentioning
confidence: 94%